1995
DOI: 10.1111/j.1365-2125.1995.tb04404.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual and group dose‐responses to intravenous omeprazole in the first 24 h: pH‐feedback‐controlled and fixed‐dose infusions.

Abstract: 1. Individual responses to intravenous boli of omeprazole have shown considerable variability. Data on the individual responses to the new omeprazole infusion formulation are lacking. 2. Individual dose‐ responses in the first 24 h of fixed‐dose and pH‐feedback‐controlled infusions of omeprazole were assessed in two randomised, third‐party blinded, cross‐over studies, using two separate groups of eight healthy subjects. In study A, feedback‐controlled infusions of omeprazole (target pH 5, dose range 0‐12 mg h‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Only two of these studies compared an 80 mg loading dose to a 40 mg loading dose. One clearly demonstrated the superiority of the higher dose, 106 while the other did not 111 . However, this second study did show that the 80 mg loading dose improved the consistency of the antisecretory effect and reduced the dose requirement in most subjects during the fasting period.…”
Section: The Role Of Acid Suppressionmentioning
confidence: 70%
See 1 more Smart Citation
“…Only two of these studies compared an 80 mg loading dose to a 40 mg loading dose. One clearly demonstrated the superiority of the higher dose, 106 while the other did not 111 . However, this second study did show that the 80 mg loading dose improved the consistency of the antisecretory effect and reduced the dose requirement in most subjects during the fasting period.…”
Section: The Role Of Acid Suppressionmentioning
confidence: 70%
“…A loading dose of 80 mg followed by continuous infusion of 8 mg/h of omeprazole or pantoprazole has been shown to be highly effective in rapidly and consistently maintaining pH above 6.0 in the stomach (Table 2). 79 , 106 , 110 –112 In a study comparing four dosage regimens for pantoprazole, the 80 mg loading dose plus continuous infusion of 8 mg/h achieved the highest median percentage time above pH 6.0 (84%) ( Figure 4). 106 This was superior to bolus administration of 40 mg every 8 h (0%) or continuous infusion of 4 mg/h after initial administration of one or two bolus injections of 40 mg (13% and 31%, respectively).…”
Section: The Role Of Acid Suppressionmentioning
confidence: 99%
“…It is unclear whether more rapid initi-8 mg/h of OME or PAN has been shown to be highly effective in rapidly and consistently maintaining pH 6.0 ation of therapy, both endoscopic and medical, would offer additional benefits. An effective regimen appears to in the stomach [47,[74][75][76][77]. In a study of IV PAN, Brunner et al [74] found that this dose was able to maintain pH be a loading dose of 80 mg administered by bolus injection followed by 8 mg/h by CI for at least 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…SCH28080 binds to the E 2 or E 2 P form of the enzyme and is a strictly K ϩ -competitive inhibitor (Wallmark et al, 1987;Mendlein and Sachs, 1990). This mechanism allows rapid inhibition of the pump without the need for acidity at its luminal surface because the pump is blocked in midcycle without a requirement for pump activity, thus preventing transient acidic excursions (Wilder-Smith et al, 1995). However, because inhibition is reversible, with either a relatively short plasma half-life or rapid dissociation of the drug, acid secretion rapidly returns to pretreatment levels, reducing efficacy of oncea-day dosing.…”
Section: Introductionmentioning
confidence: 99%